Efficient delivery of DNA into bovine preimplantation embryos by multiwall carbon nanotubes. - MUNK, M. (2016)
The pellucid zone (PZ) is a protective embryonic cells barrier against chemical, physical or biological substances. This put, usual transfection methods are not efficient for mammal oocytes and embryos as they are exclusively for somatic cells. Carbon nanotubes have emerged as a new method for gene delivery, and they can be an alternative for embryos transfection, however its ability to cross the PZ and mediated gene transfer is unknown. Our data confirm that multiwall carbon nanotubes (MWNTs) can cross the PZ and delivery of pDNA into in vitro-fertilized bovine embryos. The degeneration rate and the expression of genes associated to cell viability were not affected in embryos exposed to MWNTs. Those embryos, however, had lower cell number and higher apoptotic cell index, but this did not impair the embryonic development. This study shows the potential utility of the MWNT for the development of new method for delivery of DNA into bovine embryos.